Mutant HTT does not affect glial development but impairs myelination in the early disease stage - Yang, Sitong; Ma, Jingjing; Zhang, Han; Chen, Laiqiang; Li, Yuxuan; Pan, Mingtian; Zhu, Hongcheng; Liang, Jun; He, Dajian; Li, Shihua; Li, Xiao-Jiang; Guo, Xiangyu (Frontiers in Neuroscience, 2023)
Introduction: Huntington's disease (HD) is caused by expanded CAG repeats in the huntingtin gene (HTT) and is characterized by late-onset neurodegeneration that primarily affects the striatum.Several studies have shown that mutant HTT can also affect neuronal development, contributing to the late-onset neurodegeneration. However, it is currently unclear whether mutant HTT impairs the development of glial cells, which is important for understanding whether mutant HTT affects glial cells during early brain development.Methods: Using HD knock-in mice that express full-length mutant HTT with a 140 glutamine repeat at the endogenous level, we analyzed the numbers of astrocytes and oligodendrocytes from postnatal day 1 to 3 months of age via Western blotting and immunocytochemistry. We also performed electron microscopy, RNAseq analysis, and quantitative RT-PCR.The numbers of astrocytes and oligodendrocytes were not significantly altered in postnatal HD KI mice compared to wild type (WT) mice. Consistently, glial protein expression levels were not significantly different between HD KI and WT mice. However, at 3 months of age, myelin protein expression was reduced in HD KI mice, as evidenced by Western blotting and immunocytochemical results. Electron microscopy revealed a slight but significant reduction in myelin thickness of axons in the HD KI mouse brain at 3 months of age. RNAseq analysis did not show significant reductions in myelin-related genes in postnatal HD KI mice.Conclusions: These data suggest that cytoplasmic mutant HTT, rather than nuclear mutant HTT, mediates myelination defects in the early stages of the disease without impacting the differentiation and maturation of glial cells.